Pelatihan Pengelolaan Digitalisasi Perpustakaan SDN Pandanwangi 5 Kota Malang: Library Digitalization Management Training Pandanwangi 5 Elementary School in Malang City - Sultoni, Sultoni; Sunarni, Sunarni; Sunandar, Asep; Benty, Djum Djum Noor (PengabdianMu: Jurnal Ilmiah Pengabdian kepada Masyarakat, 2025)
Community Service activities are to increase the usefulness of the school library as a learning resource for teachers and students. This activity aims to increase knowledge and concepts about school library management for elementary school teachers and instill teachers' skills in managing and utilizing libraries as learning resources. The method used is lecture/counseling which contains the delivery of information for general and theoretical material (school library management material); dialogic method which is in the form of questions and answers and discussions about how to manage a school library; and training techniques to instill technical and practical skills and skills in school library management, and provide a concrete picture in the field of school library management. As a result, training participants gained additional knowledge about managing elementary school libraries based on digitalization. The library management training program received a positive response from teachers at Pandanwangi 5 Malang State Elementary School. Furthermore, the well-established institutional cooperation between the Malang State University FIP, especially the Department of Educational Administration, and the Pandanwangi 5 Malang State Elementary School is expected to continue as part of the Tri Darma of Higher Education.